Graded Index Chalcogenide Fibers with Nanostructured Core. Issue 3 (4th February 2021) - Meneghetti, Marcello; Forestier, Xavier; Petersen, Christian R.; Kasztelanic, Rafal; Klimczak, Mariusz; Bang, Ole; Buczyński, Ryszard; Troles, Johann
Abstract : Fabrication of graded index (GRIN) fibers is for a long time limited to ion‐exchange, modified chemical vapour deposition (MCVD) or other deposition techniques. Recently, the nanostructuring of an all‐solid core in fibers has proven to be a versatile and low cost alternative for the production of gradient index optical fibers. Herein, high purity chalcogenide glasses in the Ge‐As‐Se glass system, synthesized in‐house, are used for stacking and drawing chalcogenide nanostructured GRIN fibers designed using the Maxwell‐Garnett effective medium theory, simulated annealing and genetic algorithms. The successful generation of a supercontinuum spanning the mid‐infrared from 3 to 6 μm, pumping at a central wavelength of 4 μm using an Optical Parametric Oscillator with femtoseconds pulses, is also reported. Abstract : Herein, high purity chalcogenide glasses in the Ge‐As‐Se glass system, are used for stacking and drawing nanostructured graded index fibers designed using the Maxwell‐Garnett effective medium theory, simulated annealing and genetic algorithms. Generation of a supercontinuum spanning the mid‐infrared from 3 to 6 μm, pumping at a central wavelength of 4 μm is also reported.